Learners' writing approaches in the context of first and second language use - KARABINAR, SELMA (ELSEVIER SCIENCE BV, 2013)
The construct of writing approaches has been used to describe the relationship between the beliefs that writers have about writing and the patterns of strategies that they employ. The aim of the research is to investigate university students' conception of writing as deep and surface processes in L1 and L2 in Turkey. Students' writing approaches were measured through the Inventory of Processes in College Composition (IPIC) developed by Lavelle (1993). It can be concluded that deep approach is more frequent than the surface approach in both L1 and L2 but deep approach scores in L1 is higher than it is in L2. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of ALSC 2012
Keywords: writing approaches; surface approach; deep approach; academic writing; SELF-REGULATION